Chinese and Turkish Parents' Reflective Parenting: Accelerating Shifts in Contemporary Parenting During Pandemic Contexts - Lehner-Mear, Rachel; Xu, Yuwei; Liu, Chang; Yu, Yun; TORAN, MEHMET; Sak, Ramazan; Sahin-Sak, Ikbal Tuba (Routledge Journals, Taylor & Francis Ltd., 2025)
During the COVID-19 pandemic, particularly during periods of quarantine, parents and children were sometimes together in ways which contrasted their pre-pandemic life. This paper uses a reflective parenting lens and processual approach to analyse the quarantine experiences of twenty-four parents of three-to-six-year-olds from China and T & uuml;rkiye, gathered in semi-structured interviews. The paper reveals not only that Chinese and Turkish parents were reflective but that such reflections engaged with contemporary shifts in parenting, in particular: (i) the role of the parent; (ii) 'fixing' the child; (iii) the parent-child hierarchy; and (iv) grandparent involvement in parenting. The practicalities of the pandemic context are shown to enhance social evolution towards reflective parenting by increasing parent-child interaction. The paper also highlights that practising reflective parenting is sometimes challenging, uncomfortable and partial. Structural issues in Chinese and Turkish contemporary life which hinder reflective parenting are highlighted, including working patterns, grandparent involvement, and social scripts that interact with parenting practices. Reflective parenting, assumed to be less common in these contexts, may be inhibited by structural dimensions which had reduced impact in the quarantine period. However, when parents are reflective, they define their own practices and resist, at least in part, traditional notions of parenting.
Keywords: China; Covid-19 Quarantine; Intensive Parenting; Parent–child Relationship; Reflective Parenting; Türkiye